Analisis Sistem Agribisnis Padi Sawah di Kawasan Ekowisata (Studi Kasus Subak Sembung, Desa Peguyangan, Kecamatan Denpasar Utara) - DEWI, LISTIANA; DARMAWAN, DWI PUTRA; SUAMBA, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Analysis of Wetland Rice Agribusiness System in Ecotourism Area (A Case Study of Subak Sembung, Peguyangan Village, District of North Denpasar) The existence of subak land conversion in Denpasar City causes Denpasar Mayor to issue a policy to protect rice fields through development of Green Open Zone, especially rice fields for ecotourism purposes. Subak Sembung is a subak that becomes ecotourism area in the middle of the town. It is necessary to do research to analyze the system of wetland rice agribusiness in an ecotourism area. The purpose of this study was to determine the system of wetland rice agribusiness, profits and feasibility of rice field farming, as well as obstacles in the development of rice farming in Subak Sembung. The method used was qualitative descriptive analysis and quantitative descriptive analysis in the form of cost analysis, income, as well as analysis of revenue and cost balance. The results showed that upstream agro-industry subsystem, farming system, downstream agroindutrial subsystem, and supporting institution subsystem had a good relation. There is a special support institution (Subak Sembung ecotourism manager) that provides additional ecological and economic value through the sharing of the results of ecotourism management. The farmers did not receive a direct share of the management of ecotourism, but the farms earned a profit of Rp. 6,996,784.20 / ha, as well as the revenue and expense of 2.88. Obstacles faced by farmers were in the form of labor shortage of rice field tractor and pest insulation aphis. The conclusion of the research is the system of wetland rice agribusiness in Subak Sembung has been running quite well, rice farming is able to gain profits and said feasible to run in the future, and farmers experience barriers in the management of the farm.